New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957 - Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2019)
Helicopsyche has about 270 extant species widely distributed, with highest species diversity in tropical and subtropical areas. Currently, the genus is divided into six subgenera, with only two of them occurring in the Neotropical region. In Brazil, 28 species of Helicopsyche have been recorded, being nine in Cochliopsyche and 19 in Feropsyche. In this paper, we describe, diagnose and illustrate six new species of Helicopsyche subgenus Feropsyche from Rio de Janeiro state, Brazil: Helicopsyche bendego sp. nov., H. daome sp. nov., H. dinoprata sp. nov., H. luziae sp. nov., H. petri sp. nov., and H. shaamunensu sp. nov. Furthermore, H. (F.) planorboides is redescribed based on the holotype and additional specimens; the type series of this species is now deposited in the collection of the Departamento de Zoologia, Instituto de Biologia, Universidade Federal do Rio de Janeiro. Finally, Helicopsyche (F.) catoles, H. (F.) guara and H. (F.) planorboides are reported for the first time from Rio de Janeiro state, Brazil, the last one also listed for Espírito Santo state, Brazil.